THE DIAGNOSTIC CRITERIA FOR ARTERIAL HYPERTENSION IN CHILDREN AND ADOLESCENTS - Yuldasheva Gulnoz Giоzovna; Nasimova Dinara Usmon qizi. (Western European Studies, 2024)
This article describes etiopatogenesis, clinic and criteria for the diagnosis of arterial hypertension in children and adolescents. Types and methods of measurement of arterial hypertension in children are described. Given normal blood pressure and measures of protection of hypertension depending on age
Keywords: arterial hypertension; teenager; diagnostic criteria